Repeated Administration of D-Amphetamine Induces Distinct Alterations in Behavior and Metabolite Levels in 129Sv and Bl6 Mouse Strains - Vanaveski, Taavi; Narvik, Jane; Innos, Jürgen; Philips, Mari-Anne; Ottas, Aigar; Plaas, Mario; Haring, Liina; Zilmer, Mihkel; Vasar, Eero (Frontiers in Neuroscience, 2018)
The main goal of the study was to characterize the behavioral and metabolomic profiles of repeated administration (for 11 days) of d-amphetamine (AMPH, 3 mg/kg i.p.), indirect agonist of dopamine (DA), in widely used 129S6/SvEvTac (129Sv) and C57BL/6NTac (Bl6) mouse strains. Acute administration of AMPH (acute AMPH) induced significantly stronger motor stimulation in Bl6. However, repeated administration of AMPH (repeated AMPH) caused stronger motor sensitization in 129Sv compared acute AMPH. Body weight of 129Sv was reduced after repeated saline and AMPH, whereas no change occurred in Bl6. In the metabolomic study, acute AMPH induced an elevation of isoleucine and leucine, branched chain amino acids (BCAA), whereas the level of hexoses was reduced in Bl6. Both BCAAs and hexoses remained on level of acute AMPH after repeated AMPH in Bl6. Three biogenic amines [asymmetric dimethylarginine (ADMA), alpha-aminoadipic acid (alpha-AAA), kynurenine] were significantly reduced after repeated AMPH. Acute AMPH caused in 129Sv a significant reduction of valine, lysophosphatidylcholines (lysoPC a C16:0, lysoPC a C18:2, lysoPC a C20:4), phosphatidylcholine (PC) diacyls (PC aa C34:2, PC aa C36:2, PC aa C36:3, PC aa C36:4) and alkyl-acyls (PC ae C38:4, PC ae C40:4). However, repeated AMPH increased the levels of valine and isoleucine, long-chain acylcarnitines (C14, C14:1-OH, C16, C18:1), PC diacyls (PC aa C38:4, PC aa C38:6, PC aa C42:6), PC acyl-alkyls (PC ae C38:4, PC ae C40:4, PC ae C40:5, PC ae C40:6, PC ae C42:1, PC ae C42:3) and sphingolipids [SM(OH)C22:1, SM C24:0] compared to acute AMPH in 129Sv. Hexoses and kynurenine were reduced after repeated AMPH compared to saline in 129Sv. The established changes probably reflect a shift in energy metabolism toward lipid molecules in 129Sv because of reduced level of hexoses. Pooled data from both strains showed that the elevation of isoleucine and leucine was a prominent biomarker of AMPH-induced behavioral sensitization. Simultaneously a significant decline of hexoses, citrulline, ADMA and kynurenine occurred. The reduced levels of kynurenine, ADMA and citrulline likely reflect altered function of N-methyl-D-aspartate (NMDA) and NO systems caused by repeated AMPH. Altogether, 129Sv strain displays stronger sensitization toward AMPH and larger variance in metabolite levels than Bl6.